2022
DOI: 10.15275/rusomj.2022.0210
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism And Gestational Diabetes Mellitus: Is There A Relationship?

Abstract: Background and Objective — Subclinical gestational hypothyroidism (SGH) and gestational diabetes mellitus (GDM) constitute two most common endocrine pathologies encountered during pregnancy. SGH and GDM have common pathophysiological mechanisms, being interrelated pathological conditions that are capable of complicating the course of pregnancy, labor and the postpartum period both on the part of the mother and on the part of the fetus. We aimed to analyze the relationship between these pathologies and to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…19 According to a study involving 2333 pregnant women, higher TSH levels and positive anti-TPO were associated with an increased risk of GDM progression. 38 In this study, around half of the total GDM patients had thyroid dysfunction, showing a significant link between GDM and hypothyroidism. No cases were found with GDM and hyperthyroidism.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…19 According to a study involving 2333 pregnant women, higher TSH levels and positive anti-TPO were associated with an increased risk of GDM progression. 38 In this study, around half of the total GDM patients had thyroid dysfunction, showing a significant link between GDM and hypothyroidism. No cases were found with GDM and hyperthyroidism.…”
Section: Discussionmentioning
confidence: 56%
“…Hornnes et al observed that women who had thyroid autoimmunity were more likely to experience pregnancy-related glucose intolerance, whereas others had opposing views. 1,32,33,[35][36][37][38][39][40] Among 6% of anti-TPO positive euthyroid patients, 2% of cases had GDM. The incidence of GDM, hypothyroidism, and anti-TPO positive cases was 3%.…”
Section: Discussionmentioning
confidence: 99%